'Because I said so?' Revisiting the 'letters' in early modern letters patent. Issue 1 (28th February 2022) - Dent, Chris
Abstract : Letters patent have been used as a tool of governance in England since medieval times – though their functions have changed. The uses to which Henry II put his were limited by the socio-political context of the feudal system. When Elizabeth I began to use them as a tool of 'economic' policy – such as handing them out to regulate trade with the continent – it was only one of a number of uses. The role of the letters in governance, including the disbursement of peerages, under Henry II and in the sixteenth to the seventeenth century are compared here. The conclusion is that their use, at the time of the passing of the Statute of Monopolies, should best be seen as the Crown sharing part of its 'body politic', bringing the patentee into the monarch's inner circle, rather than as a granting of an individual 'right'.